PENGARUH PROFITABILITAS LIKUIDITAS SOLVABILITAS TERHADAP NILAI PERUSAHAAN INDUSTRI SEMEN YANG TERDAFTAR BEI - Azzahra Mariatul Khibtiyah; Zulfikar Ramadhan (Taksasila Edukasi Insani, 2026)
This study aims to examine and analyze the influence of profitability, liquidity, solvability on firm value in the cement companies listed on the Indonesia Stock Exchange (IDX). This research is a quantitative study with an associative nature. The population in this study is cement companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The sampling technique used was purposive sampling, resulting in a sample of 5 companies. The analysis method used in this study is multiple linear regression analysis on panel data, which includes model estimation determination, estimation method, coefficient of determination test, and hypothesis testing. The results of this study indicate that profitability has a significant effect on firm value, while firm size has no significant effect on firm value.Keywords : Profitability, Likuidity, Solvability, Firm Value